Studies on Superparamagnetic Behavior of CoFe\(_2\)O\(_4\)/rGO Nanocomposites at Different Temperatures - Mishra, Amodini (Challenges and Advances in Chemical Science Vol. 5, 2021)
The source of magnetism lies due to spin and orbital motions of electrons and how the electrons relate with other. Magnetic nanomaterials have attracted considerable attention due to their important properties which differ from those of bulk materials. So, they can be used to make materials and devices with new properties. Magnetic nanoparticles display some explicit properties such as superparamagnetism. Two dimensional (2D) nanosheets such as reduced graphene oxide (rGO) possess unique properties like, high mobility, chemical active, good optically transparent and very high active surface area etc. These important properties make this material an admirable applicant to making nanocomposites with magnetic nanoparticles such as cobalt ferrite (CoFe2O4). Decorating CoFe2O4 nanoparticles on rGO will impart the needed magnetic property into nanosheets, making the nanocomposites promising for a variety of fields. This chapter discuss the properties, general methods of preparation and some characteristics of CoFe2O4/rGO nanocomposites that can be effectively used in in different applications.